(untitled) (New York, 1995)
A two-volume anthology that places the Western literary tradition and its canon within a world context. Selections are divided into 6 major literary periods, with each period subdivided into Representative Texts, Western Texts, The World Context, and Background Texts.
Keywords: Văn học,Literature; Bộ sưu tập,Collections